Assessment of efficacy and safety of imatinib as an adjunct host-targeted therapy for parasite clearance in chloroquine-resistant malaria: a prospective case control study - Fazeel Zubair Ahmed; Shaifulla P (The Egyptian Journal of Internal Medicine)
Abstract Overview Chloroquine-resistant malaria poses a significant treatment challenge, especially in endemic areas. Host-targeted therapies, like tyrosine kinase inhibitors (TKIs) such as imatinib, have shown potential to improve malaria treatment outcomes by disrupting parasite egress from red blood cells. This study investigates the efficacy and safety of imatinib as an adjunct therapy to accelerate fever reduction and parasite clearance in male patients with chloroquine-resistant malaria. Patients and methods This open-label, prospective, randomized case–control study was conducted on 60 male patients aged 18–50, diagnosed with chloroquine-resistant malaria at Viswabharathi Medical College, India. Patients were randomized into two groups: a control group receiving standard anti-malarial therapy and a test group receiving standard therapy plus imatinib (400 mg daily for 3 days). Efficacy endpoints included the time to reduce parasite load by half and normalization of body temperature. Safety assessments monitored adverse reactions throughout the treatment period. Results The imatinib group demonstrated a significantly faster reduction in fever, with normalization by day 2 compared to day 3 in the control group (p < 0.05). Parasite counts decreased more rapidly in the imatinib group, with mean levels falling to below 1000 parasites/mcl by day 3. Mild adverse effects, primarily headaches and gastrointestinal symptoms, were reported but resolved by day 3 with no severe events directly attributed to imatinib. Conclusion Imatinib as an adjunct therapy may enhance the efficacy of standard anti-malarial treatments by accelerating parasite clearance and fever reduction in cases of chloroquine-resistant malaria. These findings support further investigation into TKIs as a complementary approach to existing malaria treatments, particularly in regions facing drug resistance challenges.